On some modifications and applications of the post correspondence problem - Sahla, Esa (fi=Turun yliopisto|en=University of Turku|, 2022)
The Post Correspondence Problem was introduced by Emil Post in 1946. The problem considers pairs of lists of sequences of symbols, or words, where each word has its place on the list determined by its index. The Post Correspondence Problem asks does there exist a sequence of indices so that, when we write the words in the order of the sequence as single words from both lists, the two resulting words are equal. Post proved the problem to be undecidable, that is, no algorithm deciding it can exist. A variety of restrictions and modifications have been introduced to the original formulation of the problem, that have then been shown to be either decidable or undecidable. Both the original Post Correspondence Problem and its modifications have been widely used in proving other decision problems undecidable. In this thesis we consider some modifications of the Post Correspondence Problem as well as some applications of it in undecidability proofs. We consider a modification for sequences of indices that are infinite to two directions. We also consider a modification to the original Post Correspondence Problem where instead of the words being equal for a sequence of indices, we take two sequences that are conjugates of each other. Two words are conjugates if we can write one word by taking the other and moving some part of that word from the end to the beginning. Both modifications are shown to be undecidable. We also use the Post Correspondence Problem and its modification for injective morphisms in proving two problems from formal language theory to be undecidable; the first problem is on special shuffling of words and the second problem on fixed points of rational functions.